COVID-19 pneumonia and tocilizumab use - Cáceres-Bernaola, Ursula (2020)
We present the case of a 44-year-old male patient, health personnel with high blood pressure, who had contact with patients with COVID-19 pneumonia. He had rapidly clinically-radiologically progressive lung involvement, received evidence-based treatment at admission, and an interleukin-6 receptor antagonist (tocilizumab) for compassionate use, obtaining a favorable clinical response.